2008
DOI: 10.1080/02705060.2008.9664218
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Daily Consumption and Specific Daily Metabolic Demand of Juvenile Flathead Catfish (Pylodictis olivaris)

Abstract: Maximum daily consumption and spccific daily metabolic demand were determined for juvenile flathead catfish (Pylodictis olivaris) in the laboratory over a temperature range of 3-32 "C. Maximum daily consumption increased with increasing water temperature, was significantly higher at 19 "C than at colder temperatures, and remained elevated up to 32 "C. Fish rarely ate below 15 "C, most stopped feeding at I I "C, and no fish consumed anything at 7 "C or below. Specific daily metabolic demand showed a gradual inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Based solely on basal metabolic demand 1,000 unexploited individuals would require 100,600,000 more calories during a 200 day season than 1,000 exploited individuals. This caloric demand is equivalent to the caloric content of 86.7 kg of Bluegill ( Lepomis macrochirus ) [ 51 ] or 142.5 kg of Fathead Minnow ( Pimephales promelas) [ 52 ]. The effects that such energetic differences among exploited and unexploited individuals have on a systems trophic dynamics would of course be modulated by system productivity and other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Based solely on basal metabolic demand 1,000 unexploited individuals would require 100,600,000 more calories during a 200 day season than 1,000 exploited individuals. This caloric demand is equivalent to the caloric content of 86.7 kg of Bluegill ( Lepomis macrochirus ) [ 51 ] or 142.5 kg of Fathead Minnow ( Pimephales promelas) [ 52 ]. The effects that such energetic differences among exploited and unexploited individuals have on a systems trophic dynamics would of course be modulated by system productivity and other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming there is no local adaptation to temperatures, a lack of feeding by Flathead Catfish and minimal prey activity should occur at temperatures <10 C (Fast and Momot 1973;Brown and Fitzpatrick 1978;Bourret et al 2008). In the upper Gila River, our lower elevation sites had over a month (40 d) longer with water temperatures greater than this 10 C threshold than did the upper sites.…”
Section: Discussionmentioning
confidence: 99%
“…Given that juvenile Flathead Catfish (<100 mm) are primarily insectivores (Etnier and Starnes 1993;Jackson 1999), they were excluded from bioenergetics modeling. Feeding was assumed to occur only when water temperatures were above 10 C because Flathead Catfish feeding and movement have not been documented at lower temperatures (Daugherty and Sutton 2005;Bourret et al 2008). Also, prey activity is minimal to none below 10 C (Fast and Momot 1973;Brown and Fitzpatrick 1978).…”
Section: Methodsmentioning
confidence: 99%
“…The seasonal patterns in consumption predicted by the general bioenergetics model were consistent with laboratory studies on juvenile flathead catfish. Bourret et al [24] found that daily consumption of juvenile flathead catfish increased with higher temperatures and remained elevated at high temperatures (32°C). Bourret et al [24] also found that consumption of juvenile flathead catfish declined under 19°C with limited consumption below 15°C.…”
Section: Discussionmentioning
confidence: 99%
“…Bourret et al [24] found that daily consumption of juvenile flathead catfish increased with higher temperatures and remained elevated at high temperatures (32°C). Bourret et al [24] also found that consumption of juvenile flathead catfish declined under 19°C with limited consumption below 15°C. Our simulations predicted that the majority of flathead catfish consumption occurred from late May through August when temperatures were above 25°C and minimal consumption occurred between October and March when average temperatures were below 19°C.…”
Section: Discussionmentioning
confidence: 99%